Aktivitas Penyembuhan Luka Sayatan Sediaan Salep Ekstrak Etanol Daun Patiwala (Lantana camara L.) - Nuralifah Nuralifah; Nur illiyyin Akib; Rifa’atul Mahmudah; Fery Indradewi Armadany; Parawansah Parawansah; Indah Amalia Lestari (State University of Gorontalo, 2022)
Patiwala (Lantana camara L.) contains flavonoid compounds, tannins, and saponins which are efficacious as a wound healer. Research on activities test of the incision wound healing ointment preparations from patiwala leaf ethanol extract (Lantana camara L.) aims to know the wound healing activity of ointment slices of ethanol extract of patiwala leaves in male white rabbits, as well as knowing the potential irritation of ointment preparations from ethanol extract of patiwala leaves in humans. Phytochemical screening was done by the color testing reaction method. The ointment formulation was carried out by the smelting method using vaseline album and cera alba base with a concentration of 4% extract. The incision wound healing activity test was performed with the Morton method using a rabbit test animal. The irritation test was carried out using the patch test method on 12 panelists. Phytochemical screening results prove that the patiwala leaves contain flavonoid compounds, tannins, and saponins which are efficacious as wound healers. The best activity test results on wound healing in rabbits are incision ointment of patiwala ethanol extract at 4% concentration with 100% healing time for 10,3 days. The results of the irritation test showed that the ointment extract of patiwala leaves proved to be non-irritating so it was safe to use. It was concluded that the ethanol extract of 4% patiwala leaves had activity as a wound healing wound.